The roles of the human SETMAR (Metnase) protein in illegitimate DNA recombination and non-homologous end joining repair - Tellier, M; Chalmers, R (Elsevier, 2019)
SETMAR is a fusion between a SET-domain methyltransferase gene and a mariner-family transposase gene, which is specific to anthropoid primates. However, the ancestral SET gene is present in all other mammals and birds. SETMAR is reported to be involved in transcriptional regulation and a diverse set of reactions related to DNA repair. Since the transcriptional effects of SETMAR depend on site-specific DNA binding, and are perturbed by inactivating the methyltransferase, we wondered whether we could differentiate the effects of the SET and MAR domains in DNA repair assays. We therefore generated several stable U2OS cell lines expressing either wild type SETMAR or truncation or point mutant variants. We tested these cell lines with in vivo plasmid-based assays to determine the relevance of the different domains and activities of SETMAR in DNA repair. Contrary to previous reports, we found that wild type SETMAR had little to no effect on the rate of cell division, DNA integration into the genome or non-homologous end joining. Also contrary to previous reports, we failed to detect any effect of a strong active-site mutation that should have knocked out the putative nuclease activity of SETMAR.